Current Understanding of the Pathophysiology of Myocardial Fibrosis and Its Quantitative Assessment in Heart Failure - Tong Liu; Deli Song; Jianzeng Dong; Pinghui Zhu; Jie Liu; Jie Liu; Wei Liu; Xiaohai Ma; Lei Zhao; Shukuan Ling (Frontiers in Physiology, 2017)
Myocardial fibrosis is an important part of cardiac remodeling that leads to heart failure and death. Myocardial fibrosis results from increased myofibroblast activity and excessive extracellular matrix deposition. Various cells and molecules are involved in this process, providing targets for potential drug therapies. Currently, the main detection methods of myocardial fibrosis rely on serum markers, cardiac magnetic resonance imaging, and endomyocardial biopsy. This review summarizes our current knowledge regarding the pathophysiology, quantitative assessment, and novel therapeutic strategies of myocardial fibrosis.